Importancia del nitrógeno para el crecimiento, desarrollo y rendimiento del cultivó de café (Coffea spp.) en Ecuador - Ube Anchundia, Jorge Luis (2021)
The cultivation of coffee is an activity of outstanding economic, social and environmental importance. Coffee in this country means income generation for coffee growers, collectors, transporters and marketers, as well as foreign exchange earnings that help boost the rural economy in producing territories. Nitrogen is essential for plant growth and high coffee production. Absorption occurs in the early phase during foliar development and flowering. Among the functions of nitrogen are: it is part of protein molecules, participates in the transfer of genetic information and in photosynthesis and experiences great mobility in the plant. Nutrient applications are highest during peak fruit productivity, typically three years and up. It is in this phase that the export of nutrients in the fruits is greatest. To carry out the execution of this document, an investigation of bibliographic information of scientific articles, web pages and digital technical manuals was carried out. This information is very important for readers to understand the importance of nitrogen for growth and development in coffee cultivation.